Efeitos Hipotensor e Vasorrelaxante do Óleo Essencial de Lippia microphylla Cham. e de seu Constituinte Principal Timol: Envolvimento do Bloqueio de Canais para Cálcio - Araújo, Islania Giselia Albuquerque (2011)
The genus Lippia (Verbenaceae) has yielded a great number of medicinal and economically important species that are frequently used in folk medicine for treatment of several diseases, such as: coughs, bronchitis, liver disorders and hypertension. L. microphylla Cham. is a plant of the genus Lippia found in the Northeast of Brazil, and there is no information in the literature concerning its cardiovascular effects. Therefore, this study aimed to evaluate the cardiovascular effects of the essential oil of L. microphylla Cham. (EOLM) and of its main constituent, thymol. In normotensive non-anaesthetized rats, EOLM injections produced hypotension (ED50=5.5 (4.1-7.3) mg/Kg, n=5) and bradycardia (ED50=5.2 (4.3-6.2) mg/Kg, n=5). Isometric tension recordings revealed that EOLM (1 300 μg/mL) caused concentration-dependent relaxation in isolated mesenteric rings, with functional endothelium, pre-contracted with phenylephrine (10 μM) (EC50=28.2 (25.3-31.4) μg/mL, n=5) and this effect was not attenuated by removal of the vascular endothelia layer. In preparations without endothelium, pre-incubated with KCl 20 mM, the relaxantion was not changed. Furthermore, EOLM caused relaxation in mesenteric rings pre-contracted with KCl 60 mM and inhibited Ca2+ -induced vasoconstriction in a concentration-dependent manner. In addition, EOLM relaxed the contractions elicited by the L-type Ca2+ channel activator, S(-)-Bay K 8644, indicating that the vasodilatation is related to the inhibition of Ca2+ influx through L-type Ca2+ channels. To confirm this hypothesis, whole-cell L-type Ca2+ currents were recorded in freshly dispersed rat mesenteric artery myocytes. EOLM (1-100 μg/mL) significantly inhibited Ba2+ currents in a concentration-dependent manner (EC50=11.9 (9.4-15.0) μg/mL, n=4).These results suggest that OELM induce vasorelaxant effect in rat mesenteric artery due to the inhibition of the Ca2+ influx via voltage-dependent L-type Ca2+ channels. Interestingly, the relaxantion induced by thymol (EC50=9.3 (8.3-10.4) μg/mL, n=5, p<0.01) was more potent than that observed to EOLM (EC50=23.9 (22.0-26.0) μg/mL, n=5), indicating that the vascular actions of EOLM could be attributed to its main constituent, thymol. The cardiovascular responses evoked by thymol were investigated in SHR and WKY rats. In SHR and WKY non-anaesthetized rats, intravenous administration of thymol (0.1; 0.3; 1; 3; 6; 12 and 15 mg/Kg, i.v.) produced hypotension and bradycardia in a dose-dependent manner. Isometric tension recordings, the pharmacological profile of arterial relaxant effects of thymol was compared in rings of mesenteric arteries and aorta from SHR and WKY. In preparations without endothelium, thymol (1 μM 1 mM) produced relaxation in mesenteric arteries from SHR (pD2=4.40.04, n=5) and WKY (pD2=4.30.02, n=5) and aorta from SHR (pD2 = 4.40.03, n=5) and WKY (pD2=4.30.03, n=5) and this effect was not altered in preparations with functional endothelium. Furthermore, thymol relaxed the vasoconstriction induced by high K+ solution, U46619 and S(-)-Bay K 8644 in mesenteric arteries and aorta from SHR and WKY. The addition of thymol also inhibited Ca2+ -induced vasoconstriction in a concentration-dependent manner in mesenteric and aorta segments from SHR and WKY. In electrophysiological recordings, L-type Ca2+ current (ICa,L) was decreased by thymol in a concentration-dependent manner in cardiomyocytes isolated from SHR (pD2=3.40.06, n=4, p<0.05) and WKY (pD2=4.70.05, n=4). In addition, thymol lowed-down both the fast and slow time constants for L-type Ca2+ current inactivation. In conclusion, these results suggest that the vascular effects induced by EOLM and thymol are probably due to the inhibition of the Ca2+ influx via voltage-dependent L-type Ca2+ channels.